Vimentin and cytokeratin expression in nodular hyperplasia and carcinoma of the prostate. Issue 11 (November 1995) - Heatley, M; Maxwell, P; Whiteside, C; Toner, P
Abstract : AIM--To assess the value of vimentin and cytokeratin (CK) intermediate filament proteins (IFPs) in distinguishing between nodular hyperplasia and carcinoma of the prostate and in predicting prognosis in prostatic cancer. METHODS--Fifteen carcinomas and 49 cases of nodular hyperplasia were studied using frozen sections and monoclonal antibodies to CK and vimentin IFPs. RESULTS--There was no statistically significant difference in vimentin expression between nodular hyperplasia and carcinoma. The luminal epithelium in both also reacted with antibodies which detect CK8, 18 and 19. CK 7 expression was found in 57% of cases of nodular hyperplasia and was not identified in any carcinoma. There was a reaction with antibodies to CK1, 2, 3, 4, 10, 11, and 13 in only a minority of cases. There was no statistically significant difference in vimentin and CK reactivity in high and low grade carcinomas. CONCLUSION--Neither vimentin nor CK expression assists in establishing whether a prostatic lesion is benign or malignant or in predicting the biological behaviour of a prostatic carcinoma.